LOCAL POWER & POLITICS IN INDONESIA : Decentralisation & Democratisation - Fealy, Greg, 1957-; Aspinall, Edward (Book collections on Project MUSE., 2003)
Indonesia is experiencing an historic and dramatic shift in political and economic power from the centre to the local level. The collapse of the highly centralised Soeharto regime allowed long-repressed local aspirations to come to the fore. The new Indonesian Government then began one of the world's most radical decentralisation programmes, under which extensive powers are being devolved to the district level. In every region and province, diverse popular movements and local claimants to sta ...